2021
DOI: 10.1186/s40337-021-00381-0
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers in anorexia nervosa treatment initiation: a qualitative study on the perspectives of patients, carers and professionals

Abstract: Background An early psychotherapeutic treatment of anorexia nervosa (AN) is crucial for a good prognosis. In order to improve treatment initiation, knowledge about facilitators and barriers to treatment is needed. Objective Against this background, we aimed to identify facilitators and barriers from the perspectives of patients, carers and professionals using a qualitative approach. Method To this end,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 50 publications
(21 reference statements)
2
35
0
2
Order By: Relevance
“…These experiences are consistent with the Arts et al Study that showed that AN online information was often of variable quality and difficult to read [ 64 ]. Even more, and especially for adolescents, not understanding the disorder and the need for treatment is a real obstacle in implementing appropriate treatment [ 9 ]. It was therefore expected that having a single source of reliable data on the disorder or on dietary facts would limit this risk and facilitate communication with caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These experiences are consistent with the Arts et al Study that showed that AN online information was often of variable quality and difficult to read [ 64 ]. Even more, and especially for adolescents, not understanding the disorder and the need for treatment is a real obstacle in implementing appropriate treatment [ 9 ]. It was therefore expected that having a single source of reliable data on the disorder or on dietary facts would limit this risk and facilitate communication with caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Social influence, as was discussed earlier, is a major parameter in building the intent to use [ 32 , 33 ]. It can therefore be influenced negatively by shame and disorder-related stigmas, which are well-known barriers to the search for help and treatment in EDs [ 8 , 9 ], and more generally in mental health care. We can thus see how important it would be that the app felt safe and “without judgement”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrument and item generation were based on a recommended procedure for mixed-methods studies [31]. Key facilitators and barriers of treatment initiation were identi ed based on 22 qualitative interviews with AN-patients, their relatives and referring health care professionals (sub-study 1 [32]). From this pool, items for the FABIANA-Checklist were derived based on prototypical illustrating quotes from the interviews.…”
Section: Development Of the Fabiana-checklistmentioning
confidence: 99%
“…As the FABIANA-Checklist explicitly refers to the time that preceded the rst psychotherapeutic treatment, it will not allow conclusions on correlates of treatment-seeking in general. The FABIANA-Checklist is based on a large sample compared to qualitative studies [32], which should guarantee that many signi cant factors were included. It is, however, conceivable that less frequently mentioned aspects might have a particularly large impact on the DUI.…”
Section: Strengths and Limitationsmentioning
confidence: 99%